1999
DOI: 10.1162/089976699300016287
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Synchronization Among Neuronal Populations and Their Mean Activity Levels

Abstract: In the past decade the importance of synchronized dynamics in the brain has emerged from both empirical and theoretical perspectives. Fast dynamic synchronous interactions of an oscillatory or nonoscillatory nature may constitute a form of temporal coding that underlies feature binding and perceptual synthesis. The relationship between synchronization among neuronal populations and the population ring rates addresses two important issues: the distinction between rate coding and synchronization coding models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 34 publications
4
78
0
Order By: Relevance
“…These findings add to an increasing body of literature suggesting that neuronal interactions result in both in phase and amplitude coupling (Bayraktaroglu et al, 2013;Chawla et al, 1999Chawla et al, , 2000Daffertshofer and van Wijk, 2011;Mehrkanoon et al, 2014). On the other hand, amplitude and phase coupling are considered to have different causes and putative functions (Engel et al, 2013), and to operate at different time scales .…”
Section: Discussionsupporting
confidence: 57%
“…These findings add to an increasing body of literature suggesting that neuronal interactions result in both in phase and amplitude coupling (Bayraktaroglu et al, 2013;Chawla et al, 1999Chawla et al, , 2000Daffertshofer and van Wijk, 2011;Mehrkanoon et al, 2014). On the other hand, amplitude and phase coupling are considered to have different causes and putative functions (Engel et al, 2013), and to operate at different time scales .…”
Section: Discussionsupporting
confidence: 57%
“…We had expected to see the converse given empirical results (e.g., Canolty et al 2006) and the simulations reported in Friston (2001). However, on reflection, the current results are entirely sensible if one considers that high (gamma) frequencies reflects increased neuronal firing (Chawla et al 1999): Heuristically, this means that gamma activity in low-level areas induces slower dynamics at higher cortical levels as prediction error is accumulated for perceptual synthesis. The concomitant high-level gamma activity (due to intrinsic nonlinear coupling) then accelerates the decay of evoked responses in the lower level that are manifest at, the population level, as damped alpha oscillations.…”
Section: Discussionmentioning
confidence: 54%
“…Computational modelling suggests that, as activity levels increase, smaller membrane time constants promote synchronous gain in the network, i.e. cells become more sensitive to temporal coincidences in their synaptic inputs, thus responding more to synchronous than to asynchronous inputs (Chawla, Lumer and Friston, 1999).…”
Section: Modulation That Synchronizes Responses To Rf Inputmentioning
confidence: 99%